Experimental and Numerical Research on Flow-Induced Vibration in Valves - Hussein, Asmaa Ali (Al-Khwarizmi Engineering Journal, 2017)
Abstract All central air conditioning systems contain piping system with various components, sizes, material, and layouts. If such systems in operating mode, the flow in piping system and its component such as valves can produce severe vibration due to some flow phenomenon’s. In this research, experimental measurements and numerical simulation are used to study the flow-induced vibration in valves. Computational fluid dynamics (CFD) concepts are included with one-way and two-way fluid-structure interaction concepts by using finite element software Package (ANSYS 14.57). Detection analysis is performed on flow characteristics under operation conditions and relations with structural vibration. Most of real geometrical, operational, and boundary conditions are simulated to obtain best similarity with real operation conditions. Comparisons performed between experimental data and numerical results (one-way and two-way simulation) to verify the results. The main conclusion was drawn from the study that the dominant source of vibration for valve is the water pulsation in addition to amount of water hammering. In addition, the main source of water pulsation in globe valve is the vortex shedding and pressure difference between upstream and downstream of valve. The vibration amplitude was increased with increasing flow rate until to be maximum when the flow rate around 30% and then decreased until flow rate reaches to around 85% and then trends to be constant. Keywords: Flow-induced vibration, vortex shedding, pressure pulsation, valve, finite element, ANSYS, fast Fourier transform (FFT).